Application of Dynamic Surcharging for Construction of Tanks on Reclaimed Ground - Hamidi, Babak; Varaksin, S.; Nikraz, Hamid (Australian Geomechanics Society, 2011)
Palm Jumeira is a reclaimed island off the coast of Dubai. While almost all heavy structures built on this island have been piled, the heaviest non-piled structures that have been constructed are two sewage treatment tanks that have used a unique and innovative Dynamic Surcharging ground improvement solution for their foundation systems. For each tank, a 4 m high surcharge was initially placed on the tank’s area and left in place for several days. Then dynamic surcharging was performed by dropping the pounder at the periphery of the surcharge embankment to induce additional settlements. The surcharge was then removed, the ground level reduced, print locations additionally excavated, and dynamic compaction was carried out. Post ground improvement Menard Pressuremeter Tests (PMT) and finite element calculations demonstrated that acceptance criteria were achieved.